Flagellar motor protein-targeted search for the druggable site of Helicobacter pylori - Tammara, Vaishnavi; Angrover, Ruchika; Sirur, Disha; Das, Atanu (Physical Chemistry Chemical Physics, 2024)
The deleterious impact of Helicobacter pylori (H. pylori) on human health is contingent upon its ability to create and sustain colony structure, which in turn is dictated by the effective performance of flagella - a multi-protein rotary nanodevice. Hence, to design an effective therapeutic strategy against H. pylori, we here conducted a systematic search for an effective druggable site by focusing on the structure-dynamics-energetics-stability landscape of the junction points of three 1 : 1 protein complexes (FliF(C)-FliG(N), FliG(M)-FliM(M), and FliY(C)-FliN(C)) that contribute mainly to the rotary motion of the flagella via the transformation of information along the junctions over a wide range of pH values operative in the stomach (from neutral to acidic). We applied a gamut of physiologically relevant perturbations in the form of thermal scanning and mechanical force to sample the entire quasi - and non-equilibrium conformational spaces available for the protein complexes under neutral and acidic pH conditions. Our perturbation-induced magnification of conformational distortion approach identified pH-independent protein sequence-specific evolution of precise thermally labile segments, which dictate the specific thermal unfolding mechanism of each complex and this complex-specific pH-independent structural disruption notion remains consistent under mechanical stress as well. Complementing the above observations with the relative rank-ordering of estimated equilibrium binding free energies between two protein sequences of a specific complex quantifies the extent of structure-stability modulation due to pH alteration, rationalizes the exceptional stability of H. pylori under acidic pH conditions, and identifies the pH-independent complex-sequence-segment-residue diagram for targeted drug design.